The missing piece of the puzzle: Liquidity premiums in inflation-indexed markets - Joost Driessen; Theo E. Nijman; Zorka Simon (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
Fleckenstein et al. (2014) document that nominal Treasuries trade at higher prices than inflation-swapped indexed bonds, which exactly replicate the nominal cash flows. We study whether this mispricing arises from liquidity premiums in inflation-indexed bonds (TIPS) and inflation swaps. Using US data, we show that the level of liquidity affects TIPS, whereas swap yields include a liquidity risk premium. We also allow for liquidity effects in nominal bonds. These results are based on a model with a systematic liquidity risk factor and asset-specific liquidity characteristics. We show that these liquidity (risk) premiums explain a substantial part of the TIPS underpricing.
urn:nbn:de:hebis:30:3-438750
Keywords: C51; G12; G01; H63; 330; liquidity premium; liquidity risk; TIPS; inflation swaps; TIPS-Treasury puzzle